Knowledge of denial and reinforcement practices an opportunity for a different pedagogy at school. - Ernell Villa Amaya; Wilmer Villa (Universidad del Magdalena, 2015)
This text is the result of a research process that addresses the knowledge of denial and the reinforcement practices within a school-community relation, which is developed from the opportunity provided by pedagogy, assumed as part of a different perspective. It is based on the need to generate an understanding-action from identifying issues affecting the school and the community. The investigation emerges from a flexible design, where the process is permanently approached to. The methodological plan is defined from the qualitative research that seeks to question the culture of actors involved, as a semiotic text; in this case, the inquiry methodology is developed parting from the ethnographic and the agreed narrative research that places the action in a horizontal relation.